Red cell size factor is a sensitive index in the early diagnosis of nondigestive tract cancer-related anemia: An observational study - Zhan, Bicui; Zhu, Yongjia; Yu, Jiahong; Zhu, Qiaojuan; Zhang, Huaying; Ye, Xiaoqiang (Medicine (Baltimore), 2024)
Cancer-related anemia (CRA) is a common comorbidity in cancer patients, and it can lead to a worse prognosis. The aim of this cross-sectional study is to investigate the clinical value of the red cell size factor (Rsf) in the early diagnosis of nondigestive tract CRA. A total of 231 patients with nondigestive tract solid cancer were included, and they were divided into anemic and nonanemic subjects according to the hemoglobin (Hb) levels. A BC-7500 blood analyzer was used to detect the indices of red blood cell and reticulocyte, and the mean corpuscular volume (MCV), mean reticulocyte volume (MRV), reticulocyte hemoglobin (RHE) content, and reticulocyte production index were observed. Subsequently, the Rsf was calculated. Receiver operating characteristic curve analysis was used to evaluate the identifying power of Rsf for anemia diagnosed by the combination of RHE and reticulocyte production index. The adjusted-multivariate analysis and quartiles were used to assess the relation of reduced Rsf level with the risk and incidence of anemia diagnosed by combining the MCV, MCH, and mean corpuscular hemoglobin concentration (MCHC), respectively. Rsf levels showed no statistical differences between anemia and nonanemia subjects grouped by Hb (P > .05). Rsf has a high correlation with the RHE level (R > 0.900, P < .001), or MCV, mean corpuscular hemoglobin (MCH), and MCHC in anemia patients (r: 0.435-0.802, P < .001). Receiver operating characteristic curves showed that Rsf had the highest overall area under curve of 0.886 (95% confidence interval: 0.845-0.927) in identifying anemia of cancer patients (P < .001). When the optimal cutoff values of Rsf were set at 97.05 fl in males and 94.95 fl in females, the sensitivity and specificity were 0.94 and 0.76, and 0.98 and 0.75, respectively. Being treated as a categorical variable, Rsf had a highest odds ratio value of 30.626 (12.552-74.726; P < .001) for the risk of anemia. The increment of Rsf quartiles was highly associated with the decreased incidence of overall anemia (P trend < 0.001). The study suggests that decreased Rsf level is a potentially powerful predictor of overt anemia in nondigestive tract cancer, and it can be used as a convenient, practical, cost-free, and sensitive index in early diagnosis of nondigestive tract CRA.